2021
DOI: 10.1186/s13148-021-01063-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of GFI1 as a mediator of the association between prenatal smoking exposure and ADHD symptoms at 6 years: the Hokkaido Study on Environment and Children’s Health

Abstract: Background Prenatal smoking exposure has been associated with childhood attention-deficit/hyperactivity disorder (ADHD). However, the mechanism underlying this relationship remains unclear. We assessed whether DNA methylation differences may mediate the association between prenatal smoking exposure and ADHD symptoms at the age of 6 years. Results We selected 1150 mother–infant pairs from the Hokkaido Study on the Environment and Children’s Health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…The DNA methylation levels were examined via next-generation sequencing t in a region of each gene. We examined whether the changes in DNA methylation mediate the association between prenatal smoking and ADHD symptoms, finding that DNA methylation of the GF11 region mediated 48.4% of the total association between maternal active smoking during pregnancy and ADHD symptoms [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA methylation levels were examined via next-generation sequencing t in a region of each gene. We examined whether the changes in DNA methylation mediate the association between prenatal smoking and ADHD symptoms, finding that DNA methylation of the GF11 region mediated 48.4% of the total association between maternal active smoking during pregnancy and ADHD symptoms [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results of the Hokkaido Study also suggest that certain chemicals alter DNA methylation in humans [ 79 82 , 102 ]. Exposure to environmental chemicals during pregnancy causes child epigenome changes at specific sites in a wide range of functional genes at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal toxic exposure affects the fetus and is one of the main determinants of early childhood development (Fernald et al, 2017; World Health Organization, UNICEF, World Bank Group, 2018). The effect of exposure may continue throughout life by epigenetics (Miyake et al, 2021). It was shown that maternal prenatal smoking influenced reading and math test scores and had a prominently negative impact on cognitive development in the long term (Anthopolos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, nutritional changes take place to supply the demands of both the mother and the foetus, and they are important for the normal development of the foetus [ 2 ]. Besides the mother’s diet, the foetus is susceptible to damage by maternal diseases, such as type 2 diabetes (T2D), obesity [ 3 , 4 , 5 ], or smoking [ 6 , 7 ], and the consumption of alcohol [ 8 , 9 ]. Under these conditions, free radicals (FR) are overproduced and accumulate in cells.…”
Section: Introductionmentioning
confidence: 99%